(untitled) (Journal of the College of Basic Education, 2024)
: The current research aims to identify: (The effect of the dual situation-based learning model in correcting incorrect grammatical concepts among fifth-grade literary students), and to achieve the goal of the current research, the researcher set the following null hypotheses: There is no statistically significant difference at a significance level of (0.05) between the average scores of the experimental group students who study Arabic grammar according to the dual situation-based learning model in correcting grammatical concepts and the average scores of the control group students who study the same subject in the usual way in the grammatical concepts correction test. There is no statistically significant difference at a significance level of (0.05) between the average scores of the experimental group students who study Arabic grammar according to the dual situation-based learning model in correcting grammatical concepts and the average scores of the control group students who study the same subject in the usual way in the grammatical concepts correction test according to the topics.There is no statistically significant difference at the significance level (0.05) between the average scores of the experimental group students in the pre-test and post-test in the test of correcting incorrect grammatical concepts. The researcher adopted the experimental design with two equivalent groups. To achieve the research objective, a purposive sample of students in the two groups was selected after exclusion (60) students. The researcher formulated (65) behavioral objectives. In light of the content of the prescribed book and the formulated behavioral objectives, he prepared (48) teaching plans for the two research groups. The researcher prepared the research tools. Thus, the paragraphs for the proposed test reached (20) multiple-choice paragraphs. He specified four alternatives for each test paragraph. The researcher verified the strength of distinction, the difficulty factor, and the effectiveness of the incorrect alternatives for each paragraph of the test using appropriate statistical methods. In light of the research results, the conclusion was reached that there is a large percentage of Arabic grammar concepts that are misunderstood by fifth-grade literary students.